Illicit discharge detection in stormwater drains using an Arduino-based low-cost sensor network. (1st February 2022) - Shi, B.; Catsamas, S.; Deletic, B.; Wang, M.; Bach, P. M.; Lintern, A.; Deletic, A.; McCarthy, D. T.
Abstract: Illicit discharges in urban stormwater drains are a major environmental concern that deteriorate downstream waterway health. Conventional detection methods such as stormwater drain visual inspection and dye testing have fundamental drawbacks and limitations which can prevent easy location and elimination of illegal discharges in a catchment. We deployed 22 novel low-cost level, temperature and conductivity sensors across an urban catchment in Melbourne for a year to monitor the distributed drainage network, thereby detecting likely illicit discharges ranging from a transitory flow with less than 10 minutes to persistent flows lasting longer than 20 hours. We discuss rapid deployment methods, real-time data collection and online processing. The ensemble analysis of all dry weather flow data across all sites indicates that: (i) large uncertainties are associated with discharge frequency, duration, and variation in water quality within industrial and residential land uses; (ii) most dry weather discharges are intermittent and transient flows which are difficult to detect and not simply due to cross-connections with the sewerage network; (iii) detectable diurnal discharge patterns can support mitigation efforts, including policies and regulatory measures (e.g., enforcement or education) to protect receiving waterways; and, (iv) that it is possible to cost effectively isolate sources of dry weather pollution using a distributed sensor network. HIGHLIGHTS: Low cost water level, temperature, electrical conductivity sensors deployed at 20+ locations in catchment. IoT based sensor server ensures network is affordable, detects dry weather anomalous discharges. Most detected discharge pulses last under an hour, making it hard to detect via traditional sensing.